Nephrotic syndrome presenting as pulmonary thromboembolism:a case report and literature review - REN Juan; HUANG Yi (Linchuang shenzangbing zazhi)
Objective To explore the clinical characteristics,diagnosis and treatment of nephrotic syndrome(NS)presenting as pulmonary thromboembolism(PTE).Methods The clinical data of nephrotic syndrome presenting as PTE was summarized,and the related literatures were reviewed.Results NS was one of the risk factors of venous thromboembolism(VTE).In the case PTE was the affliction for which the patient sought medical attention,and NS was thereafter diagnosed.The disease progressed rapidly,and a complete remission was achieved by anticoagulants combined with immunosuppressive agents.Conclusions A clinician should be alter to the underlying diseases of PTE,for example NS in this case.And the proper diagnosis of NS is essential to a better prognosis when PTE occurs.